The British are coming : the war for America, Lexington to Princeton, 1775-1777 - Atkinson, Rick (Revolution trilogy, 2019)
"Rick Atkinson, author of the Pulitzer Prize-winning An Army at Dawn and two other masterly books about World War II, has long been admired for his unparalleled ability to write deeply researched, stunningly vivid narrative history. Now he turns his attention to a new war, and in the initial volume of the Revolution Trilogy he tells the story of the first twenty months of the bloody struggle to shake free of King George's shackles. From the battles at Lexington and Concord in spring 1775 to those at Trenton and Princeton in winter 1777, the ragtag Continental Army takes on the world's most formidable fighting force and gradually finds the will and the way to win. It is a riveting saga populated by singular characters: Henry Knox, the former bookseller with an uncanny understanding of how best to deploy artillery; Nathaniel Greene, the blue-eyed bumpkin who becomes one of America's greatest battle captains; Benjamin Franklin, the self-made man who proves himself the nation's greatest diplomat; George Washington, the commander-in-chief who learns the difficult art of leadership amid the fire and smoke of the battlefield. And the British are here, too: we see the war through their eyes and their gunsights, and as a consequence the mortal conflict between the redcoats and the rebels is all the more compelling. Full of fresh details and untold stories, The British Are Coming gives stirring new life to the first act of our country's creation drama. It is a tale of heroes and knaves, of sacrifice and blunder, of redemption and profound suffering. But once begun, the war for independence can have only one of two outcomes: death or victory."--Provided by publisher.